Dempster‐Shafer theory applied to regulatory decision process for selecting safer alternatives to toxic chemicals in consumer products. (16th December 2013) - Park, Sung Jin; Ogunseitan, Oladele A; Lejano, Raul P
ABSTRACT Regulatory agencies often face a dilemma when regulating chemicals in consumer products—namely, that of making decisions in the face of multiple, and sometimes conflicting, lines of evidence. We present an integrative approach for dealing with uncertainty and multiple pieces of evidence in toxics regulation. The integrative risk analytic framework is grounded in the Dempster–Shafer (D–S) theory that allows the analyst to combine multiple pieces of evidence and judgments from independent sources of information. We apply the integrative approach to the comparative risk assessment of bisphenol‐A (BPA)‐based polycarbonate and the functionally equivalent alternative, Eastman Tritan copolyester (ETC). Our results show that according to cumulative empirical evidence, the estimated probability of toxicity of BPA is 0.034, whereas the toxicity probability for ETC is 0.097. However, when we combine extant evidence with strength of confidence in the source (or expert judgment), we are guided by a richer interval measure, (Bel(t), Pl(t)). With the D–S derived measure, we arrive at various intervals for BPA, with the low‐range estimate at (0.034, 0.250), and (0.097, 0.688) for ETC. These new measures allow a reasonable basis for comparison and a justifiable procedure for decision making that takes advantage of multiple sources of evidence. Through the application of D–S theory to toxicity risk assessment, we show how a multiplicity of scientific evidence can be converted into a unified risk estimate, and how this information can be effectively used for comparative assessments to select potentially less toxic alternative chemicals. Integr Environ Assess Manag 2014;10:12–21. © 2013 SETAC